A denaturation-free protocol for in situ visualization of short nuclear DNA sequences using padlock probes with rolling-circle amplification - Ryoyo Ikebuchi; Lu Xi; Dimitra Bouri; Valeriia Svintytska; Hanna Davies; Pawel Olszewski; Bozena Bruhn-Olszewska; Jan P. Dumanski; Ulf Landegren (PLoS ONE, 2025)
We report an approach for in situ detection of genomic DNA sequences, where transiently opening DNA duplexes are captured by circularizing DNA strands – padlock probes – that lock in place in a sequence-specific manner through the action of a DNA ligase. Reacted probes, wound around their target strands, are then replicated by rolling-circle amplification for localized fluorescence detection. The technique serves to shorten assay time and enables detection of shorter specific DNA sequences compared to standard fluorescence in situ hybridization, FISH. Genomic sequences with thousands of locally repeated copies were detected in human leukocytes with greater than 99% efficiency and less than 0.15% false positives in just a few hours. Using a longer variant of the protocol targets of as little as 36 or 112 nt were visualized, albeit at lower efficiency and with a higher false positive rate. The technique of targeting sequences in duplex DNA using padlock probes is promising for both research and clinical diagnostics.